Perumusan Kebijakan Kepala Sekolah dalam Meningkatkan Fungsi Guru di MAS Muhammadiyah 1 Medan - Muhammad Iqbal; Tri Fatimah; Mutiara Hasni; Adinda Agustina; Nurwinda Aulia Nasution; Yuda Mulia Ramadhan Sitepu (Departement of Mathematics Education, 2023)
The main goal of education is the realization of national education goals, namely elevating the life of the nation and state, how students can be the best hope for graduates if teachers lack awareness and concern and a sense of responsibility. Here the director as a leader makes the right policy. the principal who is the foundation of quality education must act as a motivator, driver, pioneer and reinforcer, and administrator. In other words, the principal is the decision maker, determines the direction of the school's goals and is one of the implementers of educational policy or the heart of the school. This article aims to find out the implementation of the principal's policy in improving the function of teachers in Mas Muhammadiyah 1 Medan. This research uses descriptive qualitative method. The data collection technique used was observation, interviews and documentation by observing directly in the field. Based on the results of data analysis, it can be found that the form of implementation of the school principal's policy is very thorough and sequential in accordance with predetermined procedures, as well as a full day system program that makes the school a plus for the community who views it and for teachers who have balanced this with their respective duties and responsibilities. each effectively and efficiently.